Effects of Bamboo Leaf Ash on the Residual Strength of Extremely High Plasticity Soils - Kabdiyono, Era Agita; Rahayu, Wiwik; Soepandji, Budi Susilo; Handika, Nuraziz; Wulandari, Sri (Engineering, Technology & Applied Science Research, 2025)
Soils with Extremely High Plasticity (EHP) are improper for structural applications due to their low shear strength and high compressibility. Therefore, the development of soil stabilizers has become a primary focus in the efforts to enhance the engineering properties of soil, thus making it suitable for construction. Recent advancements in sustainable engineering have drawn attention to using environmentally friendly stabilizers. Bamboo Leaf Ash (BLA), obtained from abundant bamboo resources, offers a great potential for soil stabilization. With silica content up to 70% as one of its main chemical components, BLA has significant potential as a pozzolanic material for soil improvement. In this study, the residual shear strength of cohesive soil under drained conditions is measured and the optimal BLA mixture variation for improving soil stability is determined. Bentonite was used as the soil sample, and the residual shear strength was evaluated utilizing a ring shear test under drained conditions. Torque was applied to the remolded specimen to generate a shear plane until a constant shear strain was achieved, representing the residual shear strength. The results revealed that the optimal variation for enhancing residual shear strength is achieved at a 5% BLA mixture, where a balance is found between plasticity reduction and soil stability improvement. The experiment results also demonstrate that BLAs can significantly enhance the engineering properties of bentonite by reducing the Plasticity Index (PI) and increasing both peak and residual shear strength.